Co-creation of value in small agribusinesses through social networks - García Salirrosas, Elizabeth Emperatriz (2020)
This research sought to know the potential for co-creation of value of agribusiness through the social networks of small rural producers. For this, a qualitative approach study was carried out, through interviews with 21 participants who are part of the AGRO RURAL Program and other specialists in digital marketing. The findings allowed us to divide the information into four categories to consider the co-creation of agricultural products: a) Potential of the producer, b) Motivation of the producer c) Feasibility of co-creation through social networks and d) Necessary conditions. It was concluded that small producers are willing to carry out co-creation actions, however, they have limitations in terms of knowledge and skills for the use of technology. In addition, the co-creation of agricultural products through social networks would be of great benefit to producers in order to build and develop brands with consumers.